Pengaruh Pendidikan Agama Islam Terhadap Praktik Ibadah Siswa di Madrasah Tsanawiyah Negeri 2 Kota Bengkulu - Nurhikma; Adi Saputra; Irwan Satria (Yayasan Darussalam Bengkulu, 2024)
The problem that occurs is that there is a gap between Islamic religious education, namely learning fiqh, akidah ahklak, and Al-Qur'an hadith with student worship practices, which are like many students who are lazy in carrying out the midday prayer and dhuha prayer, therefore with the existence of With these problems, researchers are interested in finding answers to these problems. This research is aimed at knowing the impact Islamic religious education for student worship at MTs N 2 of Bengkulu City, this research was done On February 3rd to March 19th 2022 in MTs N 2 of Bengkulu City. This research is methodical research Quantitative correlation used for research With a specific population and sample, data collection using research instruments, data analysis is properties quantitative or statistics aimed at the test A preordained hypothesis. The research sample was 22 students. Data collected with Using angkette techniques, documentation and observation. The data from the study was analyzed with a test t is its value 0,000 < 0.05 then it can be concluded that hypothesis Received () received, and also available for examination Coefficient determinations known as R square is 0,498 or 49,8 percent. So that shows That 49,8 % of student worship practices are affected by Variable religious education of Islam and 50,2 percent Is affected by another factor, which means religious education of Islam has a significant impact on practice Student worship at MTs N 2 City of Bengkulu.